2009
DOI: 10.1016/j.bioelechem.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Direct electron transfer reactions between human ceruloplasmin and electrodes

Abstract: In an effort to find conditions favouring bioelectrocatalytic reduction of oxygen by surface-immobilised human ceruloplasmin (Cp), direct electron transfer (DET) reactions between Cp and an extended range of surfaces were considered. Exploiting advances in surface nanotechnology, bare and carbon-nanotube-modified spectrographic graphite electrodes as well as bare, thiol-and gold-nanoparticle-modified gold electrodes were considered, and ellipsometry provided clues as to the amount and form of adsorbed Cp. DET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…A bulk enzyme concentration of 4 mg mL −1 was chosen, a value similar to those used in previous studies. 9,11,12 The MCOmodified Au surfaces were imaged by operating the AFM in both tapping and PFT modes (Figure 1c,d). A granular structure similar to that of clean Au was found for these surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A bulk enzyme concentration of 4 mg mL −1 was chosen, a value similar to those used in previous studies. 9,11,12 The MCOmodified Au surfaces were imaged by operating the AFM in both tapping and PFT modes (Figure 1c,d). A granular structure similar to that of clean Au was found for these surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These included both simple, long-standing explanations in the field of redox protein/metal interface electrochemistry, 13 associated with enzyme denaturation on bare Au surfaces or/and the absence of a heterogeneous ET between Au and active centers of MCOs, 14,15 as well as a sophisticated hypothesis involving the formation of inactive forms of MCOs as a result of an unnatural ET pathway resulting from enzyme orientation specifically by the trinuclear Cu cluster (Cu-T23), which was assumed to be in DET contact with the Au surfaces. 6,7,11,12,16 Recently, the well-pronounced DET-based bioelectrocatalytic reduction of O 2 on Au electrodes modified with Lc and BOx was demonstrated. It should be emphasized, however, that bioelectrocatalysis was observed only in the case of atomically planar Au(111) electrodes, 17,18 specifically modified polycrystalline Au surfaces, 19,20 and 3D (porous) Au electrodes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, non‐turnover signals for another BMCO, ceruloplasmin (Cp), were clearly observed indicating efficient DET, but pronounced bioelectrocatalytic currents for the enzyme were not registered . Based on detailed investigations of the enzyme it was suggested that the absence of bioelectrocatalysis seems to be related to the ordered mechanism of Cp function . Moreover, only very recently even MET based bioelectrocatalytic activity of this enzyme has been shown (Figure A) .…”
Section: O2 Bioelectroreductionmentioning
confidence: 99%
“…The mechanism of O 2 bioelectrocatalytic reduction by different BMCOs, e.g . BOx, plant, fungal, and bacterial Lc, was the subject of investigation in many studies . The ET mechanism is schematically presented in Figure using one of the most studied BMCOs, fungal Trametes Lc, as an example.…”
Section: O2 Bioelectroreductionmentioning
confidence: 99%